2003
DOI: 10.1021/jm030210x
|View full text |Cite
|
Sign up to set email alerts
|

An Alpha Helix Conformationally Restricted Peptide Is Recognized by Cervical Carcinoma Patients' Sera

Abstract: Human papillomavirus type 16 (HPV-16) represents the major cervical carcinoma associated virus among women, especially in Colombia. It has thus become important to develop reliable inexpensive tests for detecting the presence of this virus. It has been shown that HPV16-E7 oncoprotein structural features have three alpha-helical structures and a loop-like structure. The hydrazone link approach was used to mimic helix secondary substructures. Sera from women with invasive cervical carcinoma were tested against c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The modified peptide was found to bind to BCL-2 with a K d value of 38.8 nM via a fluorescence polarization assay, more than a sixfold increase over the unmodified BID BH3 peptide (K d = 269 nM). Additional strategies for constraining -helices, recently reported to probe protein-protein interactions, include macrolactam formation [69], disulfide bridge formation [70], and hydrogen-bond surrogate formation [71], as well as the use of , diaminoalkane crosslinking tethers [72]. These studies highlight the importance of constrained -helical secondary structure for the inhibition of a variety of protein-protein interactions.…”
Section: Constrained Helicesmentioning
confidence: 99%
“…The modified peptide was found to bind to BCL-2 with a K d value of 38.8 nM via a fluorescence polarization assay, more than a sixfold increase over the unmodified BID BH3 peptide (K d = 269 nM). Additional strategies for constraining -helices, recently reported to probe protein-protein interactions, include macrolactam formation [69], disulfide bridge formation [70], and hydrogen-bond surrogate formation [71], as well as the use of , diaminoalkane crosslinking tethers [72]. These studies highlight the importance of constrained -helical secondary structure for the inhibition of a variety of protein-protein interactions.…”
Section: Constrained Helicesmentioning
confidence: 99%
“…Such artificial helical peptides are attractive scaffolds for molecular recognition, since the main chain H-bond surrogate either blocks solventexposed recognition surface or removes important side chain functionalities. For example, one peptide analog of a human papillomavirus peptide segment was conformationally restricted to an a-helix structure using the hydrazone link (N-H=CH-CH2CH2) approach and was shown to have a very strong reaction with sera from women having invasive cervical carcinoma [87].…”
Section: Mimics Of Helical Surface and Functionmentioning
confidence: 99%
“…The rational design of peptides that incorporate certain secondary and tertiary structural characteristics has had important implications in vaccine development (30,44,45). Recently, Calvo et al (46), investigated the use of conformational epitopes from the human papillomavirus type 16-E7 oncoprotein as a diagnostic tool for identifying the presence of HPV16 in cervical cancer patients. They synthesized a series of conformational peptides as well as their linear counterparts and demonstrated that sera isolated from patients with invasive cervical carcinoma showed strong reactivity to an ␣-helical peptide.…”
Section: Fig 2 Secondary Structural Characteristics Of Chimeric Mvfmentioning
confidence: 99%